Facile and rapid synthesis of crystalline quadruply bonded Cr(ii) acetate coordinated with axial ligands. Issue 42 (6th August 2019) - Song, Intek; Koo, Jinyoung; Yoon, Seok Min
Abstract : Facile ligation of quadruply bonded Cr(ii ) acetates at the axial position under the anoxic condition and their rapid crystallization into single crystals with sub-millimeter scale. Abstract : A quadruple bond formed between d-block or f-block atoms is an interesting research topic due to its unique nature including a supershort bonding distance and narrow energy gap between δ and δ*. Among various multiply bonded complexes, quadruply bonded Cr(ii ) acetates are considered useful to control the δ–δ* energy gap by the Lewis basicity of additional ligands. However, the synthesis and preparation of the high-quality, large-sized crystals of Cr(ii ) acetates coordinated with axial ligands (Cr2 (OAc)4 L2 ) have been difficult due to their vulnerability to O2, a representative oxidizing agent under aerobic conditions. In this study, we report a facile synthesis of sub-millimeter-scale crystals of Cr2 (OAc)4 L2 by simple dissolution of Cr2 (OAc)4 in ligand solvents L. To obtain stably ligated Cr2 (OAc)4 L2, anhydrous Cr(ii ) acetates (Cr2 (OAc)4 ) were dissolved in the ligand solvents L, which was degassed of dissolved O2 . Also, sub-millimeter-scale single crystals of Cr2 (OAc)4 L2 were produced rapidly for less than an hour by the drop-drying process. The single-crystalline phase of the synthesized Cr(ii ) complexes was measured by X-ray diffraction techniques, confirming the dependency of Lewis basicity of the additional axial ligands on the Cr–Cr quadruple bond distance. Further, the Raman peaks of the quadruple bonds in Cr2 (OAc)4 L2 were observed to be red-shifted with the increased basicity of the axial ligands.